An In Vivo Fluorescence Resonance Energy Transfer-Based Imaging Platform for Targeted Drug Discovery and Cancer Therapy - Xing, Fuqiang; Ai, Nana; Huang, Shigao; Jiang, Cheng; Mughal, Muhammad Jameel; Ge, Wei; Wang, Guanyu; Deng, Chu-Xia (Frontiers in Bioengineering and Biotechnology, 2022)
In the present study, an efficient in vivo drug screening platform is established based on FRET technique. We transfected cancer cells with FRET-based caspase-3 (C3) sensor and validated the cell lines by detecting the change in FRET signal caused by the in vitro drug-induced cell apoptosis. Furthermore, the C3 expressing cancer cells were then injected into zebrafish embryos and nude mice to establish the corresponding in vivo xenograft models. We found that cancer cell lines expressing C3 were effective in detecting cell death following drug treatment, including the detection of the tipping point of apoptosis. The drug-induced cell apoptosis was also observed in both zebrafish embryos and nude mice xenograft models. Overall, the FRET-based platform, through in vivo imaging, is potentially useful to improve drug screening efficiency.